Emotional Intelligence in medical practice - Sarkar, Abu Hasan; Senapati, Janumoni (Research and Humanities in Medical Education, 2016)
Emotional Intelligence is the ability to perceive, express, understand and regulate one’s inner emotions and the emotions of others. It is considered to be a ‘must have’ competence in the workplace. Several scientific studies have proven that the application of emotional intelligence is effective in improving the teaching-learning process and that it leads to organizational growth; however, only limited work has been carried out to assess its effectiveness in the practice of medicine, especially in India. Various scales have been developed to measure emotional intelligence but they are not universally applicable because emotional intelligence depends upon culture and personal background among other factors. In recent years in India, conflicts between patients and doctors have had serious, sometimes fatal, consequences for the physician. Behavior, when faced with a potential conflict-like situation, depends to a great extent on the emotional intelligence of the physician. Emotional intelligence of medical students and medical professionals can be honed through exposure to the medical humanities which are known to promote patient-centered care. Building better physician-patient relationships might help in averting doctor-patient conflict.